Utilization of Digital Image Processing in Process of Quality Control of The Primary Packaging of Drug Using Color Normalization Method - Danang Erwanto; Sri Arttini Dwi Prasetyowati; Eka Nuryanto Budi Susila (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
In the process of quality control, accuracy is required so that the improper drug packaging is not included into the next production process. The automatic inspection system using digital image processing can be applied to replace the manual inspection system done by humans. The image captured from the vision sensor is RGB image which is then converted into grayscale. The process of converting RGB image into grayscale image is performed using the color normalization method to spread the data of RGB colors at each pixel. From the software of image processing using the color normalization method that have been created, it shows grayscale images on the drug object which have degrees of gray higher than the grayscale image section of the background when the degree of the R, G or B color of drug is higher than the degree of the R, G, B color on the background of packaging. The determination of threshold value indicates that the binary image of the drug is white and a binary image of the background of drug packaging is black.